Comparison of color‐learning rates among eight species of three insect orders (Hymenoptera, Diptera, and Lepidoptera). Issue 5 (21st June 2021) - Kandori, Ikuo; Fukada, Satoshi; Kurosaki, Tsutomu; Yokoi, Tomoyuki; Papaj, Daniel R.
Abstract: Learning plays an important role in food acquisition in a wide range of insect species. However, few studies have explored differences in the ability to learn floral cues among pollinator species across insect orders. In this study, we examined associative learning of flower color with nectar rewards for females or female workers in two bee species (an eusocial bumblebee [ Bombus ignitus ] and a solitary mason bee [ Osmia orientalis ]) and two hoverfly species ( Eristalis cerealis and E. tenax ). Prior data for females of four butterfly species ( Idea leuconoe, Argyreus hyperbius, Pieris rapae, and Lycaena phlaeas ) were included for analyses of flower color‐learning rate in a total of eight species of three insect orders (Hymenoptera, Diptera, and Lepidoptera). All eight species learned flower colors associated with food. Flower color‐learning rate was highest in B. ignitus, followed by the two larger butterflies ( I . leuconoe and A . hyperbius ), the two smaller butterflies ( P. rapae and L. phlaeas ), and the remaining species ( E. cerealis, E. tenax, and O. orientalis ). These results represent the first evidence that the ability to learn floral cues differs among flower‐visiting insects of different orders. We discuss the adaptive significance of superior learning abilities in bumblebees and butterflies and that of inferior learning abilities in the two hoverflies and mason bees. Abstract : In this study, we examined associative learning of flower color with nectar rewards in two bee species ( Bombus ignitus and Osmia orientalis ), two hoverfly species ( Eristalis cerealis and E. tenax ) and four butterfly species ( Idea leuconoe, Argyreus hyperbius, Pieris rapae, and Lycaena phlaeas ). Flower color‐learning rate was highest in B. ignitus, followed by the two larger butterflies ( I. leuconoe and A. hyperbius ), the two smaller butterflies ( P. rapae and L. phlaeas ), and the remaining species ( E. cerealis, E. tenax, and O. orientalis ).